Perceived values, customer engagement, and collective efficacy with C-A-C on group buying app’s purchase intention - Ali @ Hamid, Mass Hareeza; Mohd Said, Ridzwana; Chu, Jianhua (International journal of Academic Research in Business and Social Sciences, 2024)
The usage of group buying apps in mobile commerce marketing has experienced a significant increase on a global scale. Many enterprises recognize these apps' economic value and social benefits and consider them a crucial channel for online marketing and brand-building. Consequently, investigating consumers' purchase intention on group buying apps has arisen as a crucial aspect of the study aimed at promoting the advancement of online marketing. This study investigates the correlation between perceived value and purchase intention by integrating the Cognition-Affection-Conation (CAC) model and perceived value theory. Furthermore, it tests the mediating impact of customer engagement and the moderating influence of collective efficacy. This study collected data from 420 Chinese Millennials through purposive sampling, and the proposed framework underwent assessment through the application of partial least squares structural equation modeling (PLS-SEM). The results of the analysis yielded three significant findings. Except for adventure, perceived values and customer engagement have positively impacted the group-buying app's purchase intention. Secondly, the results demonstrated that the connection between perceived values and purchase intention was mediated by customer engagement. Most relationships between perceived values and customer engagement were supported, except for monetary value, and customer engagement exhibited the most decisive influence. Thirdly, the moderation analysis revealed that collective efficacy positively influenced the proposed relationships. The current study has identified a previously overlooked connection in the existing literature by demonstrating the mediating effect of customer engagement in linking perceived value and purchase intention, while highlighting the significance of collective efficacy as a moderating factor. This study provides pertinent insights for stakeholders regarding users' expectations of a specific OGB app. Firstly, to appeal to potential purchasers, OGB merchants should offer many benefits associated with OGB shopping. Secondly, to effectively interact with mobile shoppers belonging to the Millennial generation and ultimately encourage them to make purchases on an OGB app, it is recommended that retailers enhance their engagement strategies. Lastly, the platform should provide tools or channels to facilitate community communication and uphold users' collective efficacy beliefs, and it will facilitate group formation.